2009
DOI: 10.1590/s0103-90162009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to Fusarium oxysporum f. sp. phaseoli Brazilian race 2 in common bean

Abstract: Aiming to obtain information concerning the genetic control of the resistance of the bean (Phaseolus vulgaris L.) to the fungus Fusarium oxysporum f. sp. phaseoli, six crosses involving three resistant lines (Carioca MG, Esal 583 and Esal 566) and four susceptible to the fungus (Carioca, CNFC 10443, Uirapuru and Esal 522) were developed. The parental lines, the controls (Carioca MG and Carioca) and the F 1 , F 2 and F 3 generations were evaluated for reaction to Fusarium. For inoculation, root cuttings were im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 13 publications
1
20
0
10
Order By: Relevance
“…Há relatos de que o alelo dominante do gene Fop 1, confere resistência à raça 2, também denominada de 'Brasileira', de Fusarium (RIBEIRO; HAGEDORN, 1979). Também utilizando linhagens brasileiras, Pereira et al (2009) evidenciaram que o controle é monogênico. Contudo, a existência de outros genes de efeito menor não deve ser descartada, em razão da ocorrência de ampla variação na expressão fenotípica, conforme verificado por Pereira et al (2008).…”
Section: Resultsunclassified
“…Há relatos de que o alelo dominante do gene Fop 1, confere resistência à raça 2, também denominada de 'Brasileira', de Fusarium (RIBEIRO; HAGEDORN, 1979). Também utilizando linhagens brasileiras, Pereira et al (2009) evidenciaram que o controle é monogênico. Contudo, a existência de outros genes de efeito menor não deve ser descartada, em razão da ocorrência de ampla variação na expressão fenotípica, conforme verificado por Pereira et al (2008).…”
Section: Resultsunclassified
“…Other authors also observed dominance in the genetic control of Fusarium wilt resistance. Pereira et al (2009) evaluated six crosses involving three resistant and four susceptible lines, and observed complete dominance in Fop resistance genetic control in common bean. The same result was reported by Cross et al (2000) for two F 2 generations of crosses between Fop-resistant and Fop-susceptible Durango common bean parents.…”
Section: Performance Of Parents and F 1 Hybridsmentioning
confidence: 99%
“…Fop severity in common bean is usually evaluated only at 21 or 22 days (Pastor-Corrales and Abawi 1987, Cândida et al 2009, Pereira et al 2009). However, in evaluations performed in different years, at different locations and under different managements, as reported by Madden et al (2007), the AUDPC proved effective to differentiate genotypes.…”
Section: Performance Of Parents and F 1 Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its production is greatly hampered by Fusarium wilt disease. The disease is becoming increasingly important due to its rising levels associated with enhanced spread of the pathogen related to increased mechanization in field activities, repeated planting of similar crop in the same area and production in regular continuous cycles within a single year [10].…”
Section: Introductionmentioning
confidence: 99%